2005
DOI: 10.1002/dc.20364
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic adenoma of the breast: Case report and review of the literature

Abstract: Pleomorphic adenoma of the breast (PAB) is a very rare neoplasm. Although quite unique in its morphology, PAB shares some similarities with adenomyoepithelioma and is considered by some authors as a variant of this entity. Cytologic diagnosis of this lesion can be very challenging, especially when limited sampling is available. The differential diagnosis of PAB includes metaplastic carcinoma. On cytologic material, fibroadenoma and phyllodes tumor should also be considered within the differential diagnosis. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] The mammographic fi ndings have been reported in 11 articles. [9][10][11][12][13][14][15][16][17][18][19] The ultrasonography also has been reported in only 2 articles. 16,19 Because of its extreme rarity in the breast and of imaging fi ndings often suggestive of carcinoma, a correct preoperative diagnosis might be diffi cult.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…[1][2][3][4][5][6][7][8] The mammographic fi ndings have been reported in 11 articles. [9][10][11][12][13][14][15][16][17][18][19] The ultrasonography also has been reported in only 2 articles. 16,19 Because of its extreme rarity in the breast and of imaging fi ndings often suggestive of carcinoma, a correct preoperative diagnosis might be diffi cult.…”
Section: Discussionmentioning
confidence: 98%
“…[14][15][16] In the present case, preoperative diagnosis was a carcinoma. Lyengar et al 10 reported that a solid mass of 2.4 cm was considered suspicious for mucinous carcinoma from both the clinical and radiographic fi ndings. On the other hand, Ballance et al 14 reported that mammography showed a densely calcifi ed mass, suggesting calcifi ed fi broadenoma.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations